CLEANED-X (Comprehensive Livestock Environmental Assessment for improved Nutrition, a secured Environment, and sustainable Development along livestock value chains) tool version 3 - CGIAR Research Program on Livestock (2021)
End users in over 34 countries, from approximately 81 different organizations, have used CLEANED-X to understand the environmental impacts and trade-offs of proposed practices or development interventions. Several applications are ongoing in close collaboration with local partners: GIZ in Tunisia, FAO in Nicaragua and in all Livestock CRP priority countries.